Whistlblowing practices Malaysian public sector: a study at akota Kinabalu City Hall - Nur Nabilah Mohd. Bakri, 1993- , author (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Project Paper (Sarjana Muda Perakaunan) - Universiti Teknologi Malaysia, 2016